Atmospheric CO2 capture by algae: Negative carbon dioxide emission path. (September 2016) - Moreira, Diana; Pires, José C.M.
Highlights: Bioenergy production with algae may play an important role in CO2 mitigation. Assessment of atmospheric CO2 capture by algae was performed. Both seaweed and microalgae presents advantages regarding other biomass sources. Process integration to improve the sustainability of whole process remains a significant challenge. Abstract: Carbon dioxide is one of the most important greenhouse gas, which concentration increase in the atmosphere is associated to climate change and global warming. Besides CO2 capture in large emission point sources, the capture of this pollutant from atmosphere may be required due to significant contribution of diffuse sources. The technologies that remove CO2 from atmosphere (creating a negative balance of CO2 ) are called negative emission technologies. Bioenergy with Carbon Capture and Storage may play an important role for CO2 mitigation. It represents the combination of bioenergy production and carbon capture and storage, keeping carbon dioxide in geological reservoirs. Algae have a high potential as the source of biomass, as they present high photosynthetic efficiencies and high biomass yields. Their biomass has a wide range of applications, which can improve the economic viability of the process. Thus, this paper aims to assess the atmospheric CO2 capture by algal cultures.